4CPS-130 Use of non-specific immunoglobulins in burned paediatric patients: validation of the protocol of a tertiary hospital - Sebastià, L Betriu (Eur J Hosp Pharm, 2018)
BACKGROUND: Serious burns produce plasma extravasation which develops an important loss of immunoglobulins (Ig). In patients with a burned surface area (BSA) >15% IgG plasmatic levels decrease until 40 hours’ post-burn. PURPOSE: To evaluate the use of non-specific Ig in burned paediatric patients based on the current protocol of the hospital. MATERIAL AND METHODS: Retrospective observational study, which includes all paediatric patients with ≥15% BSA hospitalised between August 2012 and July 2017. Biodemographic data were registered as: (sex, age, weight), burn data (BSA) and Ig administration data (plasmatic levels, dose and number of administrations). The existing protocol about the use of Ig in burned paediatric patients (BSA ≥15%) was analysed. It recommends the determination of IgG 24 to 48 hours’ post-burn and the infusion of non-specific Ig (400 mg/kg) if patients have below-normal levels. RESULTS: Thirty-one patients (12 females) with a median age of 2 years (8 m – 15 y) and a weight of 13 kg (7.5–67 kg) were enrolled in the study. The median BSA was 20% (15%–55%). Eighteen patients (58%) accomplished all the recommendations specified in the protocol. Determination of IgG levels was made in 26 patients (83.9%). Eighteen (69.2%) had below-normal levels and a median BSA of 23.5% (15–55). In the subgroup of patients with BSA ≥20% (20–55) the determination was done in the 94% (15/16) and 14 (93%) who had below-normal levels. Non-specific Ig was administered in 61% (19) of the patients at a dose of 400 mg/kg. No IgG determination was repeated after the first infusion in six patients (31.6%). Seven patients with a median BSA of 46% (16–55) needed more than one Ig infusion. CONCLUSION: All patients received the dose of Ig indicated in the protocol (400 mg/kg). In patients with BSA>20%, determination of plasmatic levels is essential because it was detected that more than 90% of the patients had below–normal levels of IgG. No IgG determination after the first infusion was repeated in more than 30% of the patients, therefore a proposal to improve the protocol is the need to repeat IgG determination in all the patients who have received an infusion to corroborate the achievement of normal IgG levels. REFERENCES AND/OR ACKNOWLEDGEMENTS: Thanks to all authors No conflict of interest